Studi Simulasi Statis Struktur Desain Cradle Penopang Kokpit BAC 111 - Stefani, Windy; Firmansyah, Adi Ridho; Prasetyo, Naufal Abdurrahman; Leksonowati, Nur Fitria Pujo (Jurnal Teknologi dan Riset Terapan (JATRA), 2024)
Cradle, a lifting device used to move the Cockpit head and other aircraft parts. The aim of this research is to obtain maximum data on the cradle structure through static simulation using SolidWorks 2020 software. The research was carried out by simulation using SolidWorks 2020 software with analysis of stress, strain and safety factor calculations for the cradle structure in supporting a static load of 1400 kg. The cradle design process was made using SolidWorks software, with the cradle size being 338 cm long, 145 cm wide at the top and 297 cm at the bottom, and using ASTM A36 type channel iron material with dimensions of 150 mm x 75 mm x 6.5 mm with loading. static of 1400 kg. The simulation results show that the maximum pressure value applied to the cradle with ASTM A36 steel material is 50.206 Mpa, below the yield strength value of 250 Mpa. The maximum displacement recorded was 1,169 mm, indicating that the deformation that occurred in the cradle structure was very minimal. With a maximum cradle capacity weighing 6.97 tons and a maximum wheel load capacity of 2.7 tons